Community Structure of Echinoderms at The Intertidal Zone of Serinting Beach Special Economic Zone of Mandalika - Hidayat, Sugih Akbar; Bachtiar, Imam; Suyantri, Eni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Serinting Beach, located within the Mandalika Special Economic Zone (SEZ), is an intertidal area with high biological potential for tourism. However, studies on its Echinodermata community remain limited. The existence of this community is crucial as an indicator of coastal ecosystem health and holds potential for developing educational ecotourism, such as reef walking tours. This research aims to analyze the species richness and composition of the Echinodermata community, along with its ecological indices (diversity, evenness, and dominance). Data was collected in March 2025 using the transect-quadrat method, employing three transects perpendicular to the coastline and 15 quadrats, each measuring 2 × 5 m². The study results revealed 21 Echinodermata species, consisting of 10 genera and 9 families from four classes: Asteroidea, Ophiuroidea, Echinoidea, and Holothuroidea. The community composition was dominated by Ophiocoma scolopendrina (43.90%), Echinometra mathaei (21.33%), and Echinometra sp. (16.77%). The diversity index (H') was 1.59; the evenness index (E) was 0.62; and the dominance index (D) was 0.28. Tripneustes gratilla populations were found in low numbers and are suspected to be under pressure due to traditional reef gleaning activities. The findings of this study are expected to serve as a basis for enviromental management and the development of educational tourism, like reef walking tours, in the intertidal zone of the Mandalika SEZ.